DIVULGING YOUNG POPULATION’S WILLINGNESS TO PURCHASE GREEN PRODUCTS - Krings, Werner J.; Sharmen, Sayma; Faisal-E-Alam, Md.; Bhuiyan, Abul Bashar (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Over the past few years, the concern of growing consumer interest in green products has rapidly expanded throughout the world. This study investigates the factors influencing consumers’ purchase intention of green products. The target population of this study is the young users who are basically students from several universities in Framingham, USA. For this study, data were gathered through Google form sent by email, along with a cover letter for the respondents’ convenience. The respondents made up the final sample size of the research. They were sent invitations to participate, and their responses were gathered after their approval. A five-point Likert scale was used where ‘1’ stands for ‘Strongly Disagree’ and ‘5’ stands for ‘Strongly Agree’ to determine the item-wise questionnaire. The final sample size was n=514. Moreover, to evaluate the hypotheses, a 5% significance level and SPSS software was used to analyze the data for research. The outcome of this study shows that health consciousness, environmental awareness, and green product knowledge have a positive and significant impact on consumers’ intention to buy green products. These variables can explain 46.80% of the variance in predicting behavioral intentions to purchase green products. It is found that among the three determinants, health consciousness (β = 0.413) had the highest impact on the purchase intention of green products among young people compared to other variables. This research might provide significant clues to the manufacturers of green products that can severely influence consumers to buy eco-friendly goods for their well-being. JEL Classification Codes: D12, M31, Q50.